A New Holoplanktonic Nudibranch (Nudibranchia: Phylliroidae) from the Central Mexican Pacific - Jeimy D. Santiago-Valentín; Eric Bautista-Guerrero; Eva R. Kozak; Gloria Pelayo-Martínez; Carmen Franco-Gordo (Diversity)
Pelagic nudibranchs exemplify evolutionary convergences towards streamlined, transparent body forms adapted for life in the planktonic environment. Here, we describe a new genera and species, designated as Pleuropyge melaquensis gen. et sp. nov. This species belongs to the family Phylliroidae and is distinguished by key diagnostic characters, including a laterally positioned anus approximately one-third of the body length from the head, the absence of a cephalic disc, and an anterior hepatic caecum that is longer than the intestine. The description of P. melaquensis contributes to the classification of a third genus and a fourth species within the Phylliroidae family. This study offers novel insights into the functional and structural traits that have enabled nudibranchs to transition from benthic to pelagic environments.